Pengembangan Modul Praktikum Fisika Untuk Teknik Mesin - Haris Mahmudi; Ah. Sulhan Fauzi (Universitas Islam Madura, 2018)
The problem that many students experience is assuming that theoretical physics courses are difficult subjects because there are too many formulas that must be memorized, understanding the concepts of physics that are still lacking. While the Physics course is a support for existing courses in Mechanical Engineering, Electrical Engineering, and Industrial Engineering. This research is a development research that uses three stages, namely: (1) Preliminary research, (2) Stage of making prototypes, and (3) assessment phase. Based on the data analysis results of validation from the validator and the readability test analysis by students aspects of the appropriateness of the contents of the Basic Physics module based on problem solving the average value of 3.22 with the criteria feasible. The aspect of feasibility assessment is the presentation of the average value obtained from 3 validators of 3.55 with eligible criteria. Evaluation of the feasibility of the basic Physics module is based on overall problem solving. It is obtained that the total average value is 3.39 with feasible criteria.